The FKBP52 Cochaperone Acts in Synergy with β-Catenin to Potentiate Androgen Receptor Signaling - Storer Samaniego, Cheryl (PLoS One, 2015)
FKBP52 and β-catenin have emerged in recent years as attractive targets for prostate cancer treatment. β-catenin interacts directly with the androgen receptor (AR) and has been characterized as a co-activator of AR-mediated transcription. FKBP52 is a positive regulator of AR in cellular and whole animal models and is required for the development of androgen-dependent tissues. We previously characterized an AR inhibitor termed MJC13 that putatively targets the AR BF3 surface to specifically inhibit FKBP52-regulated AR signaling. Predictive modeling suggests that β-catenin interacts with the AR hormone binding domain on a surface that overlaps with BF3. Here we demonstrate that FKBP52 and β-catenin interact directly in vitro and act in concert to promote a synergistic up-regulation of both hormone-independent and -dependent AR signaling. Our data demonstrate that FKBP52 promotes β-catenin interaction with AR and is required for β-catenin co-activation of AR activity in prostate cancer cells. MJC13 effectively blocks β-catenin interaction with the AR LBD and the synergistic up-regulation of AR by FKBP52 and β-catenin. Our data suggest that co-regulation of AR by FKBP52 and β-catenin does not require FKBP52 PPIase catalytic activity, nor FKBP52 binding to Hsp90. However, the FKBP52 proline-rich loop that overhangs the PPIase pocket is critical for synergy.